2022
DOI: 10.3390/f13020294
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Foresters in Polish Society

Abstract: In recent years, foresters in Poland have faced a decreasing level of social acceptance. Scientists have demonstrated that core values and personal experience shape the social acceptance of foresters and their work. The aim of our study was to determine what kind of attitudes towards foresters (ATF) do Poles have? What shapes Poles’ ATF? Is recreational behavior connected to the ATF? Which foresters’ PR and educational activities have the biggest impact on peoples’ ATF? The research tool used was the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Studies that investigated gender found differences between male and female participants in terms of stated HWGM consumption (Tomasevic et al, 2018;Goguen & Riley, 2020;Niewiadomska et al, 2020), consumption frequency (Tolušić et al, 2006;Ljung et al, 2015;Tomasevic et al, 2018), declared consumed species (Burger & Gochfeld, 2002), consumption preferences (Bodnar et al, 2010) and attitudes toward HWGM Marescotti et al, 2019) and hunting (Krokowska-Paluszak et al, 2020). Overall, the results suggest that male consumers show a more positive attitude toward HWGM and hunting than female consumers and eat this product more frequently.…”
Section: Sociodemographic Variablesmentioning
confidence: 82%
See 3 more Smart Citations
“…Studies that investigated gender found differences between male and female participants in terms of stated HWGM consumption (Tomasevic et al, 2018;Goguen & Riley, 2020;Niewiadomska et al, 2020), consumption frequency (Tolušić et al, 2006;Ljung et al, 2015;Tomasevic et al, 2018), declared consumed species (Burger & Gochfeld, 2002), consumption preferences (Bodnar et al, 2010) and attitudes toward HWGM Marescotti et al, 2019) and hunting (Krokowska-Paluszak et al, 2020). Overall, the results suggest that male consumers show a more positive attitude toward HWGM and hunting than female consumers and eat this product more frequently.…”
Section: Sociodemographic Variablesmentioning
confidence: 82%
“…Considering consumers' age, the results reveal that younger consumers consume less HWGM than older consumers (Burger & Gochfeld, 2002;Ljung et al, 2015;Tomasevic et al, 2018;Krokowska-Paluszak et al, 2020). In this respect, it may be notable to look at the results reported by Burger and Gochfeld (2002) where in contrast to the other classes of participants, middle-aged consumers (35-45 years) declare that they eat less common wild species such as doves, raccoon, and squirrel.…”
Section: Moreover Tomasevic Et Al (2018) Present a Cross-cultural Inv...mentioning
confidence: 84%
See 2 more Smart Citations
“…Its introduction is carried out in the direction of fulfilling the international obligation to provide social and environmental tasks in addition to economic tasks [1][2][3]. As a result of a review of existing studies [4][5][6][7][8], it can be concluded that attempts have been made to conduct a very broad dialogue; however, there are no in-depth studies on the use of social media in communication between groups of communities involved in the production of forest products and the public. The relevance of research on the role of social media in the relationship between forest producers and Polish society is evidenced by activities highlighting the need for new forms of education, contact and even discussion.…”
Section: Introductionmentioning
confidence: 99%